Growing early peach selections under the meadow orchard system with drastic pruning - Dall'Orto, Fernando A. Campo; Ojima, Mário; Barbosa, Wilson Barbosa; Tombolato, Antonio F. Caetano; Rigitano, Orlando; Alves, Sebastião (Pesquisa Agropecuaria Brasileira, 2014)
An experiment was carried out in 1980-1982 at the Estação Experimental de Monte Alegre do Sul, SP, Brazil, to study de viability of growing peaches (Prunus persica Batsch) by the meadow orchard system, in which the trees are planted at very short distances and annually submitted to drastic pruning. The behavior of 29 early peach selections was tested at two spacings: 3 x 0.5 x 0.5 m (double row), and 3 x 0.5 m (single row), i. e., 11,428 and 6,666 plants/ha, respectively. The average yields verified at the first harvest, in October/November 1982, were 2.3 and 3.4 kg of fruits per plant, equivalent to 26.7 and 22.4 t/ha, respectively. This cultivation system will allow better yields in shorter time than those obtained from older orchards raised under the conventional growing system (6 x 5 m spacing). Among the new peach selections tested, the following stood as the most promising to the meadow orchard system: Doçura-2 (IAC 2370-3), Jóia-1 (IAC 771-1), Jóia-2 (IAC 471-1), Ouromel-2 (IAC 171-5), Ouromel-3 (IAC 471-8), IAC 4974-10, IAC 4974-23, IAC 976-6, Maravilha (Fla. 13-72) and Flordaprince (FIa. 5-2).